Investigation of metallic 3D porous scaffold prepared by selective laser sintering for dental applications - Mohammad Hossein Malekipour Esfahani; Azadeh Asefnejad (Nanochemistry Research)
In this article, the history of metal three-dimensional (3D) printing technology and various types of methods and their advantages and disadvantages were investigated. Selective laser melting (SLM) were compared in terms of consumables, working methods, limitations, capabilities and applications. By examining each method, it can be seen that the superiority of each of them depends on the materials intend to use basis of any type of light or heavy parts. The prepared sample by SLM process belongs to the family of 3D printing is fusion powder. Also, the materials used in both processes are metals that are granular. This technology is suitable for complex parts that cannot be made by traditional methods with high cost with excellent mechanical properties for the industry, plastic and dentistry application. This technique used metal 3D printing technologywith various porosity. Metal printing provides more benefits to industries every day. This technology have its own disadvantageous which is not suitable and cost-effective for manufacturing parts with traditional methods.